The Managed Heart Revisited: Exploring the Effect of Institutional Norms on the Emotional Labor of Flight Attendants Post 9/11. (October 2017) - Santin, Marlene; Kelly, Benjamin
This article examines the emotional culture of flight attendants thirty-two years after Hochschild's (1983) study, The Managed Heart. Using data collected by participant observation and informal interviews, we argue that flight attendants are empowered by post-9/11 institutional changes in security policies and as a result are using more discretion in how they perform courteous emotional labor. We put forward two interrelated concepts—the "9/11 effect" and "role shields"—to explain how a new emphasis on safety over courtesy in institutional policies provides cabin crew with a normative resource to achieve greater autonomy. We establish that flight attendants are now more assertive when they interact with passengers. By acknowledging the flight attendant's post-9/11 experience and their increase in what we label emotional agency, this study offers a historical-comparative complement to Hochschild's emphasis on emotive constraints.